Partial Reversal of Striatal Damage by Palmitoylethanolamide Administration Following Perinatal Asphyxia - Udovin, Lucas D.; Kobiec, Tamara; Herrera, María I.; Toro-Urrego, Nicolás; Kusnier, Carlos F.; Kölliker-Frers, Rodolfo A.; Ramos-Hryb, Ana B.; Luaces, Juan P.; Otero-Losada, Matilde; Capani, Francisco (Frontiers in Neuroscience, 2020)
Perinatal asphyxia (PA) is a clinical condition brought by a birth temporary oxygen deprivation associated with long-term damage in the corpus striatum, one of the most compromised brain areas. Palmitoylethanolamide (PEA) is a neuromodulator well-known for its protective effects in brain injury models, including PA, albeit not deeply studied regarding its particular effects in the corpus striatum following PA. Using Bjelke et al. (1991) PA model, full-term pregnant rats were decapitated, and uterus horns were placed in a water bath at 37°C for 19 min. One hour later, the pups were injected with PEA 10 mg /kg s.c., and placed with surrogate mothers. After 30 days, the animals were perfused, and coronal striatal sections were collected to analyze protein level expression by western blot and the reactive area by immunohistochemistry for neuron markers: Phosphorylated Neurofilament-Heavy/Medium-chain (pNF-H/M) and Microtubule Associated Protein-2 (MAP-2), and the astrocyte marker, Glial fibrillary acidic protein (GFAP). Results indicated that PA produced neuronal damage and morphological changes. Asphyctic rats showed a decrease in pNF-H/M and MAP-2 reactive areas, GFAP+ cells number, and MAP-2 as well as pNF-H/M protein expression in the striatum. Treatment with PEA largely restored the number of GFAP+ cells. Most important, it ameliorated the decrease in pNF-H/M and MAP-2 reactive areas in asphyctic rats. Noticeably, PEA treatment reversed the decrease in MAP-2 protein expression and largely prevented PA-induced decrease in pNF-H/M protein expression. Perinatal asphyxia did not affect the GFAP protein level. Treatment with PEA attenuated striatal damage induced by PA, suggesting its therapeutic potential for the prevention of neurodevelopmental disorders.